2016
DOI: 10.4028/www.scientific.net/kem.677.181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Modulus of Elasticity of Different Types of Concrete Compared with Eurocode 2

Abstract: The comparison of really measured compressive strength static modulus of elasticity with table values stated in Eurocode 2 is essential part of the paper. Since the standard draws from modulus of elasticity - concrete strength class, the set compressive strengths will be classified in concrete particular classes. Experimental part was based on several concrete design compositions differing in particular input raw-materials. Monitored values were set with concretes in different ages with final value 180 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…It was observed that with an increase in the concrete grade of GPC, the observed difference was higher (see Figure 5(a) at 50 MPa, for instance). Regarding Figure 5(b) for comparison with empirical equations in the literature, similar observations could be deduced when comparing with Al-Amawee et al 57 Malaikah, 58 Nematzadeh and Naghipour, 59 Pintea and Onet, 60 Ispir et al, 61 Křížová and Hela, 62 Jones and McCarthy, 63 Chitrala et al, 29 and Carrasquillo et al 66 However, the values of elastic modulus of GPC in this study were higher than those measured by Swaddiwudhipong et al, 64 Lizarazo et al, 65 Diaz, 67 Cui et al, 68 and Hardjito et al 69 The difference might come from the composition of the substances in the fly ash-based GP binder or the elastic modulus of aggregates.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It was observed that with an increase in the concrete grade of GPC, the observed difference was higher (see Figure 5(a) at 50 MPa, for instance). Regarding Figure 5(b) for comparison with empirical equations in the literature, similar observations could be deduced when comparing with Al-Amawee et al 57 Malaikah, 58 Nematzadeh and Naghipour, 59 Pintea and Onet, 60 Ispir et al, 61 Křížová and Hela, 62 Jones and McCarthy, 63 Chitrala et al, 29 and Carrasquillo et al 66 However, the values of elastic modulus of GPC in this study were higher than those measured by Swaddiwudhipong et al, 64 Lizarazo et al, 65 Diaz, 67 Cui et al, 68 and Hardjito et al 69 The difference might come from the composition of the substances in the fly ash-based GP binder or the elastic modulus of aggregates.…”
Section: Resultssupporting
confidence: 80%
“…Various models were proposed to estimate the elastic modulus of concrete in function of the cylindrical compressive strength, including standards such as AS 3600, 49 AIJ, 50 ASSHTO 2007, 51 ACI 363-11, 52 EN 2004, 53 NZS 3101, 54 CSA A23.3, 55 NS 3473, 56 or empirical equations such as the ones proposed in Al-Amawee et al 57 Malaikah, 58 Nematzadeh and Naghipour, 59 Pintea and Onet, 60 Ispir et al 61 Křížová and Hela, 62 Jones and McCarthy, 63 Swaddiwudhipong et al 64 Lizarazo et al 65 Chitrala et al, 29 Carrasquillo et al, 66 Diaz, 67 Cui et al, 68 and Hardjito et al 69 The details of these formulations are presented in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Peningkatan modulus elastisitas beton akan terlihat dari umur 7 hari hingga 28 hari. Dalam periode 28 hingga 90 hari tidak akan terjadi perubahan begitu signifikan (Křížová & Hela 2016).…”
Section: Prediksi Modulus Elastisitasunclassified